2021
DOI: 10.1159/000516077
|View full text |Cite
|
Sign up to set email alerts
|

Social Support and Functional Decline in the Oldest Old

Abstract: <b><i>Objective:</i></b> Longitudinal studies investigating the link between social support and functional decline are limited among the oldest old. Thus, the aim of this study was to examine whether changes in social support are associated with functional decline among the oldest old longitudinally using panel regression models. <b><i>Methods:</i></b> Longitudinal data from 3 waves (waves 7, 8, and 9) of a multicenter prospective cohort study covering primary ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
16
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 70 publications
2
16
0
1
Order By: Relevance
“…When we consider levels of social isolation and loneliness separately, our findings are consistent with those regarding the oldest-old [53,73]. In the present sample, nearcentenarians and centenarians tended, on average, to have a number of meaningful social relationships just above the risk threshold and to report loneliness rarely.…”
Section: Discussionsupporting
confidence: 85%
“…When we consider levels of social isolation and loneliness separately, our findings are consistent with those regarding the oldest-old [53,73]. In the present sample, nearcentenarians and centenarians tended, on average, to have a number of meaningful social relationships just above the risk threshold and to report loneliness rarely.…”
Section: Discussionsupporting
confidence: 85%
“…Moreover, there was no association between social isolation and incident dementia in men or women. There are a few studies that have also examined the association between social isolation and dementia or cognitive functioning in the oldest old (23,36,37). A study also based on AgeCoDe/AgeQualiDe data examined oldest-old, healthy individuals over a period of 4.7 years with regards to social isolation and cognitive function.…”
Section: Discussionmentioning
confidence: 99%
“…It was shown that smaller social networks, measured with the LSNS-6, were associated with lower cognitive function (23). In addition, Hajek et al (37) studied oldest-old individuals based on AgeCoDe/AgeQualiDe data with the LSNS-6 over a 2-year period and found that a social network size was associated with functional deterioration in men. The different findings in comparison to our study could be explained by varying methodological approaches.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The results from the NHANES also suggest that poor sleep quality is associated with lower physical functioning among older adults, and the association is stronger among those with cognitive impairment and other chronic conditions (Puri et al, 2017). Previous research studies also suggest that lack of a support network might have negative impact over time on physical functioning among older adults (Hajek et al, 2021).…”
Section: Introductionmentioning
confidence: 99%